2021
DOI: 10.1080/21505594.2021.1878747
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induced by Vip3Aa has a pro-survival role in Spodoptera frugiperda Sf9 cells

Abstract: Vip3Aa is an insecticidal protein that can effectively control certain lepidopteran pests and has been used widely in biological control. However, the mechanism of action of Vip3Aa is unclear. In the present study, we showed that Vip3Aa could cause autophagy in Sf9 cells, which was confirmed by the increased numbers of GFP-Atg8 puncta, the appearance of autophagic vacuoles, and an elevated Atg8-II protein level. Moreover, we found that the AMPK-mTOR-ULK1 pathway is involved in Vip3Aa-induced autophagy, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…The results here do not support a substantial role in the resistance of DH-R to Vip3Aa for six genes previously reported to affect responses to Vip3Aa in S. frugiperda ( 46 50 ). In previous work with S. frugiperda , using CRISPR/Cas9 to knock out the gene encoding the receptor protein ABCC2 caused resistance to Cry1Ab and Cry1Fa ( 37 , 51 , 52 ) but CRISPR/Cas9 KOs of scavenger receptor-C or fibroblast growth factor receptor did not affect susceptibility to Vip3Aa ( 53 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results here do not support a substantial role in the resistance of DH-R to Vip3Aa for six genes previously reported to affect responses to Vip3Aa in S. frugiperda ( 46 50 ). In previous work with S. frugiperda , using CRISPR/Cas9 to knock out the gene encoding the receptor protein ABCC2 caused resistance to Cry1Ab and Cry1Fa ( 37 , 51 , 52 ) but CRISPR/Cas9 KOs of scavenger receptor-C or fibroblast growth factor receptor did not affect susceptibility to Vip3Aa ( 53 ).…”
Section: Discussioncontrasting
confidence: 99%
“…It has recently invaded Africa, Asia, and Australia ( 44 ), and it has evolved practical resistance in the Americas to the Cry toxins in Bt crops ( 12 , 45 ). Previous work with S. frugiperda has identified three putative receptors for Vip3Aa and three proteins putatively involved in defense against Vip3Aa ( 46 50 ), but we are not aware of any evidence linking these proteins with resistance to Vip3Aa selected in the laboratory or field. Here, we report the identification of an association between resistance to Vip3Aa in S. frugiperda and downregulation of a transcription factor gene for which no role in Bt toxicity has been reported before.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…It has been reported that Vip3 protein attacked the lysosome, reduced its membrane stability, and hampered the degradation of the autophagosome (Hou et al, 2020). The Vip3Aa-induced autophagy in Sf9 cells of S. frugiperda was also confirmed through the presence of autophagic vacuoles and increased level of protein Atg8-II (Hou et al, 2021). It was found that autophagy in Sf9 cells caused by this toxic protein was mediated through the AMPK-mTOR-ULK1 pathway associated with disruption of ATP-homeostasis in treated cells.…”
Section: Autophagymentioning
confidence: 82%
“…However, only Cry proteins have been extensively studied and successfully used worldwide 7,8, 1315, 17, 51, 52 . Vip3 proteins have characteristics and mode-of-action mechanisms distinct from Cry proteins and show high insecticidal activity against lepidopteran pests and are classified as a second generation of insecticidal proteins that can be broadly applied after Cry proteins in the field 3, 22, 24, 25, 53 . However, the lack of clear understanding of the molecular mechanisms underlying their insecticidal activity severely restricts their broader application and rational development.…”
Section: Discussionmentioning
confidence: 99%